Strategy for Strengthening Assessor Competence in Recognizing Prior Learning to Improve the Quality of Religious Higher Education - Ahmad Fauzi (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The weak implementation of Prior Learning Recognition (RPL) within State Islamic Religious Universities (PTKIN) is a crucial issue hindering the accessibility and inclusivity of higher education. The main problem identified is the low literacy and competency of assessors in assessing practitioner portfolios, which is exacerbated by limited assessment instruments and quality assurance standards. This policy analysis was conducted using a descriptive qualitative method with a Policy Analysis approach that integrates the USG (Urgency, Seriousness, Growth) criteria to determine priority for problem resolution. The policy methodology also involves an analysis of William N. Dunn's criteria to evaluate various alternative solutions based on aspects of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The analysis results indicate that the root of the problem stems from the lack of practical experience of assessors in mapping cross-sector competencies due to organizational fragmentation and a rigid academic culture. Theoretical support used includes Human Capital Theory, Andragogy, and the Resource-Based View to dissect the urgency of human resource investment. As a strategic solution, this policy paper recommends the establishment of a Rector's Decree concerning Internal Assessor Governance and Certification Scheme. This policy is considered the most effective because it provides legal legitimacy, standardizes assessment operations, and ensures the integrity of recognition results. Implementation of this recommendation is expected to mitigate legal risks, standardize the quality of recognition at the study program level, and increase institutional competitiveness in providing flexible and high-quality educational services to the wider community. By strengthening the capacity of assessors, PTKIN can realize an outcomes-based educational transformation that adapts to the dynamic needs of the global workforce